2017
DOI: 10.3389/fimmu.2017.01766
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoke Increases Endothelial CXCL16-Leukocyte CXCR6 Adhesion In Vitro and In Vivo. Potential Consequences in Chronic Obstructive Pulmonary Disease

Abstract: Cardiovascular disease (CVD) is a major comorbidity in chronic obstructive pulmonary disease (COPD). Although the mechanism of its development remains largely unknown, it appears to be associated with cigarette consumption and reduced lung function. Therefore, the aim of this study was to investigate the potential link between water-soluble cigarette smoke extract (CSE)-induced endothelial dysfunction and the function of CXCL16/CXCR6 axis on the initial attachment of leukocytes, in addition to its possible imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 52 publications
2
11
0
Order By: Relevance
“…3, in sections of lung tissue from the challenged mice, CXCL16 was immunolocalized principally in the epithelial cells of the airway and also in some submucosal mononuclear cells and vascular endothelial cells. 22 OVA, IL-25, and IL-33 challenge induced elevated expression of CXCL16 at day 19, consistent with the ELISA data above.…”
Section: Expression Of Cxcl16 By Immunohistologysupporting
confidence: 88%
“…3, in sections of lung tissue from the challenged mice, CXCL16 was immunolocalized principally in the epithelial cells of the airway and also in some submucosal mononuclear cells and vascular endothelial cells. 22 OVA, IL-25, and IL-33 challenge induced elevated expression of CXCL16 at day 19, consistent with the ELISA data above.…”
Section: Expression Of Cxcl16 By Immunohistologysupporting
confidence: 88%
“…Furthermore, platelets seem to be critical for leukocyte adhesion to dysfunctional (stimulated) arterial endothelium, as leukocyte-endothelium interactions were significantly impaired when platelets were dissociated with EDTA. It is widely accepted that activated platelets can mediate the endothelial adhesion of circulating leukocytes, a characteristic feature of the dysfunctional endothelium [14,28,29,30,31]. We also found a significant enhancement in the percentage of platelet-leukocyte aggregates, which were established with almost all the leukocyte subsets investigated in a background of PH.…”
Section: Discussionsupporting
confidence: 70%
“…Manzur-Jattin et al (2016) have indicated that erythrocyte eryptotic forms such as stomatocytes and spherocytes, exposing phosphatidylserine out of the membrane have higher chance to adhere to endothelium through the transmembrane chemokine CXCL16 (Borst et al, 2012), eventually promoting thrombus formation. In this context, it has recently been reported that cigarette smoke increases endothelial CXCL16-leukocyte CXCR6 adhesion in vitro and in vivo (Marques et al, 2017).…”
Section: Discussionmentioning
confidence: 97%